Una revisión sistemática de los efectos positivos de la narración de cuentos para la competencia lingüística del inglés como lengua extranjera - Pérez Agustín, Mercedes; de-la-Peña, Cristina (Bordón. Revista De Pedagogía, 2026)
Digital storytelling is an enriching pedagogical strategy that promotes lan-guage proficiency or literacy in monolingual educational contexts. However, there is a lack of studies that show comparative evidence based on quantitative data on the positive effects of digital storytelling/storytelling for foreign language teaching in a bilingual or non-bilingual educational context. The purpose of this research is to determine the positive effects of the use of digital storytelling/storytelling for foreign teaching in a bilingual or non-bilingual En-glish context regarding linguistic competence (oral and written skills). METHOD. To achieve this goal, a search of scientific literature from 2000 to the present was carried out in the data-bases Scopus, Web of Science, ERIC, Scielo and Dialnet. RESULTS. The results obtained indi-cate improvements in oral and narrative skills with the use of ST and STD in all educational stages and more proficiency on language proficiency in secondary education and university in non-bilingual contexts. DISCUSSION. These empirical results suggest the useful implications of ST and STD in monolingual contexts in various languages to increase the academic, person-al and professional development in line with the SDGs of the 2030 Agenda. INTRODUCCIÓN. La narración digital es una estrategia pedagógica enriquecedora que promueve la competencia lingüística/ o la alfabetización en contextos educativos monolingües. Sin embargo, faltan estudios que muestren evidencias comparativas basadas en datos cuantitativos sobre los efectos positivos de la narración digital para la enseñanza de lenguas extranjeras en un contexto educativo bilingüe o no bilingüe. El propósito de esta investigación es determinar los efectos positivos del uso del storytelling/storytelling digital para la enseñanza de lenguas extranjeras en un contexto bilingüe o no bilingüe de inglés en relación con la competencia lingüística (destrezas orales y escritas). MÉTODO. Para alcanzar este objetivo, se realizó una búsqueda de literatura científica desde el año 2000 hasta la actualidad en las bases de datos Scopus, Web of Science, ERIC, Scielo y Dialnet. RESULTADOS. Los resultados obtenidos indican mejoras en las destrezas orales y narrativas con el uso de ST y STD en todas las etapas educativas y un mayor dominio de la lengua en educación secundaria y universidad en contextos no bilingües. DISCUSIÓN. Estos resultados empíricos sugieren las implicaciones útiles de ST y STD en contextos monolingües en varios idiomas para aumentar el desarrollo académico, personal y profesional en línea con los ODS de la Agenda 2030.
A SYSTEMATIC REVIEW OF THE POSITIVE EFFECTS OF STORYTELLING FOR THE LINGUISTIC COMPETENCE OF ENGLISH AS A FOREIGN LANGUAGE
Keywords: storytelling; digital storytelling; L2; bilingualism